Strengthening health system governance through collaborative leadership to improve primary healthcare effectiveness - Luluk Widarti (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Collaborative leadership has become increasingly important in strengthening health system governance and improving primary healthcare effectiveness. This study aimed to analyze the influence of collaborative leadership on governance quality and primary healthcare effectiveness within decentralized healthcare settings. Methods: A quantitative cross-sectional analytical study was conducted among 320 healthcare professionals from selected primary healthcare centers in Eastern Indonesia between January and April 2026. Participants were selected using multistage cluster sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) with a significance level of α = 0.05. Results: Collaborative leadership significantly influenced governance quality (β = 0.64; 95% CI: 0.52–0.73; p < 0.001) and primary healthcare effectiveness (β = 0.41; 95% CI: 0.28–0.55; p < 0.001). Governance quality also significantly improved healthcare effectiveness (β = 0.48; 95% CI: 0.37–0.60; p < 0.001). Conclusion: Collaborative leadership strengthens governance quality and supports more responsive, accountable, and effective primary healthcare services. Strengthening participatory governance strategies may improve healthcare system sustainability and service integration